Crop Species Mechanisms and Ecosystem Services for Sustainable Forage Cropping Systems in Salt-Affected Arid Regions - Ashilenje, Dennis S.; Amombo, Erick; Hirich, Abdelaziz; Kouisni, Lamfeddal; Devkota, Krishna P.; El Mouttaqi, Ayoub; Nilahyane, Abdelaziz (Frontiers in Plant Science, 2022)
Soil salinity limits crop productivity in arid regions and it can be alleviated by crop synergies. A multivariate analysis of published data (n = 78) from arid and semiarid habitats across continents, was conducted to determine crop species mechanisms of salinity tolerance and synergies relevant for designing adapted forage cropping systems. Halophyte (Cynodon plectostachus (K. Schum.) Pilg.) and non-halophyte grasses (Lolium perenne L. and Panicum maximum Jacq.) clustered along increasing soil salinity. Halophytic grasses (Panicum antidotale Retz. and Dicanthum annulatum (Forssk.) Stapf) congregated with Medicago sativa L., a non-halophytic legume along a gradient of increasing photosynthesis. Halophytic grasses (Sporobolus spicatus (Vahl) Kunth, and Cynodon plectostachyus (K. Schum.) Pilg.) had strong yield salinity correlations. Medicago sativa L. and Leptochloa fusca L. Kunth were ubiquitous in their forage biomass production along a continuum of medium to high salinity. Forage crude protein was strongly correlated with increasing salinity in halophytic grasses and non-halophytic legumes. Halophytes were identified with mechanisms to neutralize soil sodium accumulation and forage productivity along increasing salinity. Overall, halophytes-non-halophytes, grass-forbs, annual-perennials, and plant-bacteria-fungi synergies were identified which can potentially form cropping systems that can ameliorate saline-soils and sustain forage productivity in salt affected arid regions.